Penggunaan Media Video Animasi Berbasis Capcut sebagai Media Dakwah dalam Pembelajaran PAI di Sekolah Dasar - Desi Marliani Rahmania; Anisatul Haq Mustafa; Hana Fitriani; Sariten Handayati; Ani Nur Aeni (Departement of Mathematics Education, 2023)
This research was conducted based on several problems that occur in elementary schools, one of which is the saturation of students during the learning process. Where students feel bored if learning is only done with the lecture method. Therefore this study aims to see how far the effectiveness of the use of CapCut-based animated video media as a da'wah learning media in PAI learning in elementary schools. The method used in this study is the Design and Development (D&D) method. The research sample consisted of 5th graders at SDN Overtime Situ, with a total of 23 students. The material that we provide is about